2015
DOI: 10.3109/09637486.2015.1077785
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, amylolytic enzymes inhibition and antioxidant properties of bread incorporated withStevia rebaudiana

Abstract: Wheat bread with sucrose content replaced with different levels of stevia extract was compared with traditional wheat bread. The ability to reduce glucose intake was highlighted by performing enzymatic assays using α-amylase and α-glucosidase. Antioxidant activity was measured by determining the scavenging effect on α,α-diphenyl-β-picrylhydrazyl radical. In comparison with the control, the bread with stevia extract was softer and had lower microbial growth during the shelf-life study. The sensory test showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As the world grapples with escalating concerns about sugar consumption and its associated health risks, Stevia's importance in the global sweetener market continues to grow. Numerous researchers have revealed that Stevia has a number of health advantages in addition to its sweetening properties, including anti-diabetic, anti-obesity, anti-tumor, anti-hypertensive, antimicrobial, anti-caries, and antioxidant qualities [1,2]. Nevertheless, while Stevia rebaudiana holds significant promise, its commercial cultivation encounters numerous obstacles such as suboptimal growth, restricted yields, and vulnerability to various environmental stressors, notably soil salinity.…”
Section: Introductionmentioning
confidence: 99%
“…As the world grapples with escalating concerns about sugar consumption and its associated health risks, Stevia's importance in the global sweetener market continues to grow. Numerous researchers have revealed that Stevia has a number of health advantages in addition to its sweetening properties, including anti-diabetic, anti-obesity, anti-tumor, anti-hypertensive, antimicrobial, anti-caries, and antioxidant qualities [1,2]. Nevertheless, while Stevia rebaudiana holds significant promise, its commercial cultivation encounters numerous obstacles such as suboptimal growth, restricted yields, and vulnerability to various environmental stressors, notably soil salinity.…”
Section: Introductionmentioning
confidence: 99%